1994
DOI: 10.1111/j.1365-2265.1994.tb02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with GHRH(1‐29)NH2 in children with idiopathic short stature induces a sustained increase in growth velocity

Abstract: Short-term therapy with twice-daily s.c. injection of GHRHa (20 micrograms/kg) promoted linear growth in short children who were not GH-insufficient. The improved height velocity was sustained throughout the 12 months of treatment, followed by catch-down growth, and returned to pretreatment velocity after cessation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…CInicians have questioned whether long-term CHRP administration causes desensitization of the receptor and leads to a progressively reduced hGH output, as has been reported for GHRH in rats (12) and in man (6)(7)(8). This action could interfere with the biological and metabolic effects of this new class of drugs (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…CInicians have questioned whether long-term CHRP administration causes desensitization of the receptor and leads to a progressively reduced hGH output, as has been reported for GHRH in rats (12) and in man (6)(7)(8). This action could interfere with the biological and metabolic effects of this new class of drugs (13).…”
Section: Discussionmentioning
confidence: 94%
“…The aim of this study was to investigate whether long-term intranasal hexarelin administration induces a desensitization of its receptor, similar to the effect reported for growth hormone-releasing hormone (GHRH) (6)(7)(8), and, if so, whether a reduction in hGH also reduces IGF-I synthesis and the metabolic and biological effects of this new drug.…”
mentioning
confidence: 95%
“…The mode of administration, dose of GHRH used and length of GHRH therapy has varied considerably in these studies (Table 4). The growth-promoting effect of GHRH has Treatment of GH deficiency with GHRH 575 ᭧ 1997 Blackwell Science Ltd, Clinical Endocrinology, 46, 571-578 also been demonstrated in children with idiopathic short stature (Kirk et al, 1994) treated with a dose of 20 g subcutaneously twice daily, or a continuous subcutaneous infusion of 60 ng/kg/min (86 . 4 g/kg/day) .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of several short-term positive results, clinical trials of longer duration have shown that these agents did not increase growth or adult height. More recently, short-term clinical trials with GHRH or GHreleasing peptides (GHRPs) have been performed, which appear to have led to some increase of height velocity [127][128][129][130]. However, no long-term results have been reported.…”
Section: Other Pharmaceutical Agentsmentioning
confidence: 99%